Incidence of acute respiratory infections in preschool children in an outpatient setting before and during Covid-19 pandemic in Lombardy Region, Italy - Chiara Mameli; Marina Picca; Roberto Buzzetti; Maria Elisabetta Pace; Raffaele Badolato; Claudio Cravidi; Gian Vincenzo Zuccotti; Paola Marchisio; for the Italian Society of Paediatrics Lombardy Section (BMC, 2022)
Abstract Introduction The incidence of acute respiratory tract infections (ARTIs) in children is difficult to estimate because they are typically treated in outpatient settings and the majority of epidemiological data originate from hospital settings and refer to the most severe illnesses. Therefore, the incidence of ARTIs in a real-world setting remains largely unexplored. Therefore, this study aims to estimate the incidence of ARTIs, upper respiratory tract infections (URTIs), and lower respiratory tract infections (LRTIs) in children aged 0-5 years in an outpatient setting. Methods This prospective cohort study was conducted in Lombardy, Italy, from October 1st, 2019, to March 31st, 2021, before and during the COVID-19 pandemic that began in March 2020. Caucasian healthy children aged 0-5 years were recruited from 69 Family Pediatricians (FP) and followed-up in an outpatient setting. Data were collected whenever a child was referred to FP and ARTI was diagnosed (Covid-19 related ARTI were excluded). The primary outcome was an estimate of the incidence of ARTIs. The incidence of ARTIs in different age groups and the effect of the COVID-19 pandemic on the incidence of ARTIs were secondary outcomes. Results We enrolled 484 children, 249 male (51.8%), mean age of 2.39 ± 1.68 years. The mean estimated incidence of ARTIs was 12.1/100 children × 30 days (95% CIs: 9.5-12.9), with the highest value observed in infants aged 1-12 months (24.9/100 children × 30 days; 95% CIs: 17.6-28.9). The mean estimated incidence of URTIs was higher than that of LRTIs (8.3 - CIs: 7.6-8.9 vs 3.8/100 children × 30 days - CIs: 6.4-4.3, respectively). The comparison of ARTIs, which occurred in the pre-pandemic winter, to those measured during the COVID-19 pandemic, revealed an impressive 82.1% drop in the incidence rate (CIs: 77.8-85.7). Conclusions This study showed that infants aged 1-12 months are more likely to develop ARTIs than older children and that COVID-19 pandemic has dramatically altered the epidemiology of ARTIs in children aged 0-5 years.